Open democracy reinventing popular rule for the twenty-first century - Landemore, Hélène, 1976- (Princeton University Press, 2020)
"To the Ancient Greeks, democracy meant gathering in a public space and arguing based on an agenda set by a randomly selected assembly of 500 other citizens. To the Icelandic Vikings in Northern Europe a few centuries later, it meant gathering every summer in a large field, a place where they held their own annual "parliament," and similarly talking things through until they got to relatively consensual decisions about the common's fate. Our contemporary representative democracies are very different. Modern Parliaments are intimidating buildings that are much harder to access for ordinary citizens-quite literally. They are typically gated and guarded, and it often feels as if only certain types of people-people with the right suit, accent, bank account, connections, even last names-are welcome to enter them. In Open Democracy, Landemore revitalizes the model of success from ancient open democracies alongside the problems of the present-day representative democracies in order to get to the heart of the issues which contemporary democratic societies are dealing with today. Something has been lost between the two, Landemore argues: accessibility; openness to the ordinary man and woman. Landemore believes the move to "representative" democracy, a mediated form of democracy seen as unavoidable in mass, commercial societies, also became a move towards democratic closure, and exclusivity. Open Democracy asks how can we recover the openness of ancient democracies in today's world, and would it help the crisis of democracy? In diagnosing what is wrong with representative democracy, Landemore offers a normative alternative and strategy-one that is more true to the democratic ideal of "government of the people, by the people, for the people." This alternative conception (open democracy) is one Landemore believes can be used to imagine and design more participatory, responsive, accountable, and smarter institutions, thereby strengthening our democracies along with on the whole, our societies"--